POTENSI BAKTERI ENDOFIT ASAL TANAMAN LADA SEBAGAI PELARUT FOSFAT DAN PENGIKAT NITROGEN SERTA PENGHASIL IAA / Potency of Endophytic Bacteria from Black Pepper as Phosphate Solubilization, Nitrogen Fixation and IAA Production - Gusmaini Gusmaini; Andriana Kartikawati (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
The potential of endophytic bacteria to promote plant growth has been already well known. However, research on indigenous endophytic bacteria from wild or cultivated pepper plants are still limited. The research was conducted in Microbiology Laboratory and Glass House of Research Institute for Spice and Medicinal Crops, Bogor, West Java from June 2015 to April 2016. The objective of this study was to isolate and characterize the potential of endophytic bacteria from cultivated and wild pepper plants as phosphate (P) solubilizing, N2 fixation, and IAA hormone producers. Endophytic bacteria were isolated from the roots and leaves of both cultivated and wild pepper plants. The surfaces part of plant samples were sterilized using alcohol 70% and sodium hypochlorite 2%. Healthy parts of plants (roots and leaves) are selected as samples. Then, 1 g of plant part was crushed into small particles, extracted, filtered and cultured on Trypticase Soy Agar medium, with 3 replications for each dilution. All bacterial isolates were assessed their capability as P solubilizing, N2 fixation, and IAA hormone producer. The result showed the different capability of each endophytic bacteria derived from cultivated and wild pepper plants in promoting plant growth. The results of isolation of endophytic bacteria were obtained by 23 isolates from P. nigrum and 11 isolates from P. colubrinum. The endophytic bacteria could be grouped as followed: four isolates were IAA producers; 21 isolates possessed two functions (10 isolates as N2 fixation and IAA producers, while 11 isolates as P solubilizing, and IAA producers); and nine isolates have three functions as P solubilizing, N2 fixation, and IAA producer viz. Ca3(1)2, La0(2)1, La2(2)2, La4(1)3, La4(3)1, La4(3)2, La4(3)3, La4(3)4, and Ld0(2)2. All 34 endophytic bacterial isolates obtained from this study can potentially be used to improve nutrient use efficiency and accelerate plant growth. Furthermore, it is necessary to further examine the role of endophytic bacteria, which have single or multiple functions, in improving plant growth and fertilizer use efficiency for pepper plants.Keywords : Piper nigrum, Piper colubrinum, endophytic bacteria, P solubilizing, N2 fixation, phytohormone.AbstrakPotensi bakteri endofit untuk meningkatkan pertumbuhan tanaman sudah banyak diketahui. Namun bakteri endofit indigenus tanaman lada, baik lada yang sudah dibudidayakan maupun lada liar belum banyak dilakukan penelitian. Penelitian ini dilaksanakan di Laboratorium Mikrobiologi dan Rumah Kaca Balai Penelitian Tanaman Rempah dan Obat Bogor, Jawa Barat pada bulan Juni 2015–April 2016. Penelitian bertujuan untuk mengisolasi dan mengkarakterisasi potensi bakteri endofit yang berasal dari tanaman lada budidaya dan liar sebagai pelarut P, pengikat N, dan penghasil hormon IAA in vitro. Bakteri endofit diisolasi dari akar dan daun tanaman lada budidaya dan lada liar. Permukaan sampel bagian tanaman disteril dengan menggunakan alkohol 70% dan sodium hypochlorite 2%. Bagian tanaman (akar dan daun) yang sehat dipilih sebagai contoh. Setiap bagian tanaman sebanyak 1 g ditimbang kemudian digerus sampai halus kemudian ekstraknya disaring dan ditumbuhkan pada medium Trypticase Soy Agar dengan 3 ulangan untuk tiap pengenceran. Semua isolat bakteri yang diperoleh diukur kemampuannya sebagai pelarut fosfat (P), pengikat N, dan penghasil IAA invitro. Hasil isolasi dan karakterisasi menunjukkan kemampuan setiap bakteri endofit yang berasal dari lada budidaya dan liar yang berfungsi sebagai pemicu pertumbuhan tanaman berbeda-beda. Dari hasil isolasi diperoleh sebanyak 23 isolat dari Piper nigrum dan 11 isolat dari P. colubrinum. Bakteri endofit tersebut dapat dikelompokkan menjadi penghasil IAA (4 isolat), 21 isolat berfungsi ganda (10 isolat sebagai pengikat N2 dan penghasil IAA serta 11 isolat sebagai pelarut P dan penghasil IAA), dan 9 isolat berfungsi ketiganya (pelarut P, pengikat N2 dan sekaligus penghasil IAA). Hasil penelitian mengindikasikan bahwa isolat bakteri endofit tersebut dapat dimanfaatkan untuk memacu pertumbuhan tanaman. Peran bakteri endofit tersebut perlu diuji lebih lanjut aktivitas dan kestabilannya dalam meningkatkan pertumbuhan tanaman.Kata kunci : Piper nigrum, Piper colubrinum, lbakteri endofit, pelarut P, pengikat N, fitohormon.